Santa Cristina in Caio : la lunga durata di un insediamento pubblico viario tra età romana e medioevo - Bertoldi, Stefano (Access archaeology., 2022)
This volume collects the results of the 2009-2015 excavation campaigns in Santa Cristina in Caio (Buonconvento, Siena) and contextualises the site in the wider phenomenon of mansiones, Roman secondary settlements, and their reuse between Late Antiquity and the Early Middle Ages.